Examining the Effects of Probiotics on Athletes: A Review - Gustaw Błaszczyński; Agnieszka Nowotarska; Paweł Nojek; Wiktoria Pawlik; Mariusz Zimonczyk; Monika Zawół (Journal of Education, Health and Sport)
Introduction and Objective. Probiotics, defined as live microorganisms that provide health benefits when consumed in sufficient quantities, have gained attention in the sports community. The surge in popularity of long-distance athletic competitions such as marathons, triathlons, and cycling races has led to heightened rivalry and a rising curiosity in strategies to improve sports performance. Studies have suggested that probiotics could be a valuable aid for athletes looking to improve their well-being and overall progress.